Reasons for Expiration of the Independent Guarantee - Abdulridha, Hussein; عباس, شيماء (Journal of Legal Sciences, 2025)
The independent guarantee contract, in the strict sense of contracts, is a contract that the will of the parties to the security transaction in the broad sense tended to consider as an independent contract that stood on its own, and separated it from the case of dependence known as traditional guarantees. Subordination, in the sense that the nullity, dissolution, or termination of the main relationship does not entail the expiration of the independent guarantee, or that there are reasons attributed to the creditor that lead to its expiration.It is based on this that the independent guarantee ends with the original well-known reasons for expiration or with reasons dictated by the nature of the contract itself, such as the expiry of its validity period, but the matter does not apply to its release, which is not to transgress public order, in other words, the establishment of an independent guarantee, as a guarantee of an unlawful commitment, leads to the termination of the guarantee contract accordingly expiration of the independent guarantee.